2011
DOI: 10.1111/j.1540-8175.2010.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mitral Regurgitation: Left Atrial Deformation Analysis by Two‐Dimensional Speckle Tracking Echocardiography

Abstract: Our study provides new insight for the LA function analysis in response to different degrees of MR, showing that STE measurements of LA longitudinal strain may be considered a promising tool for the early detection of impairment of LA compliance in patients with asymptomatic chronic MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 34 publications
6
79
1
Order By: Relevance
“…In addition, a negative correlation was found between the above‐mentioned STE‐derived variables and conventional echocardiographic measurements of left cardiac chamber size. These data are in agreement with previous reports focused on conventional echocardiographic assessment of LA function in dogs with MMVD,2, 7 as well as human studies in patients investigated by STE,38, 39, 40, 41, 42, 43, 44 and suggest progressive LA dysfunction with worsening of MMVD and LA dilatation. These findings might be explained by the progressive LA volume overload due to MR and remodeling and by an increase in LV filling pressures in the advanced phases of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a negative correlation was found between the above‐mentioned STE‐derived variables and conventional echocardiographic measurements of left cardiac chamber size. These data are in agreement with previous reports focused on conventional echocardiographic assessment of LA function in dogs with MMVD,2, 7 as well as human studies in patients investigated by STE,38, 39, 40, 41, 42, 43, 44 and suggest progressive LA dysfunction with worsening of MMVD and LA dilatation. These findings might be explained by the progressive LA volume overload due to MR and remodeling and by an increase in LV filling pressures in the advanced phases of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…In mitral regurgitation, PALS by STE was shown to decrease with increasing severity of mitral regurgitation (82) and was an independent predictor of mitral valve surgery and post-operative outcomes. The study by Debonnaire et al investigating 121 patients with severe primary mitral regurgitation demonstrated PALS to have the highest accuracy in identifying patients who proceeded to mitral valve surgery amongst all indices of LA function.…”
Section: Valvular Heart Diseasementioning
confidence: 87%
“…In rheumatic heart disease, a previous rheumatic illness has been shown to play a contributing role in LA and LV dysfunctions (36-38). Cameli et al (39) used a new technique of two-dimensional speckle tracking echocardiography which revealed that indicators of longitudinal LA deformation were increased in mild MR patients; however, they were decreased in moderate and severe MR patients. While the increase in mild MR patients was associated with the increase in LA compliance, the decrease in moderate and severe patients was correlated to chronic MR-related structural abnormalities such as myocyte hypertrophy, interstitial fibrosis, and reduced metalloproteinase secretion.…”
Section: Discussionmentioning
confidence: 99%